IMPACTOS DE LA INNOVACION EMPRESARIAL Y LOS DERECHOS DE PROPIEDAD INTELECTUAL EN EL MARCO DE LOS TRATADOS DE LIBRE COMERCIO - Ceballos Molano, Raquel (Cuadernos de Administración, 2006)
The globalization as a process of change towards an independent world-wide economy, with a high degree of integration and liberalization of the market, forces the States that converge to establish policies and strategies that foment the innovation and the development of the intellectual property as a growth factor. At the same time it must provide protection mechanisms to guarantee the development of the free commerce and stimulate the productivity and the competitiveness of the entrepreneurial sector, which, occuring in assymetric economies, they alloud an anticipation of the causation of damages in wide economic sectors. In this frame, the Free Trade Agreement, FTA Colombia/USA and the FTA’s in Central America and Chile, support processes of liberalization for the promotion of the commerce between the countries that in reciprocal way, offer an acces to their markets by means of the export of industrial goods and services. From another point of view, the FTA are treaties of Public International Right, therefore, for its understanding, it is necessary to know the main normative aspects that integrate them, their relation with already acquired cmmitments in other treaties and international agreements, the economic policies that they try to develop in the matter of innovation and, consequently, the rights of intellectual property –I.P.- that derive from these policies because the management of knowledge and innovation in the entrepreneurial sector are a long term motor of growth and development, that will turn into a real strategy that will contribute in a great extent to competitivity and the technological development, in order to produce new goods of export and to suitably face the challenges of Free Trade Agreement.